2022
DOI: 10.1371/journal.pgph.0000297
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of oral health conditions and treatment needs among slum and non-slum urban residents: Evidence from Nigeria

Abstract: Oral diseases constitute a neglected epidemic in Low and Middle-Income Countries (LMICs). An understanding of its distribution and severity in different settings can aid the planning of preventive and therapeutic services. This study assessed the oral health conditions, risk factors, and treatment needs among adult residents in the slum and compared findings with non-slum urban residents in Ibadan, Nigeria. The Multistage sampling was used to select adult (≥18-years) residents from a slum and a non-slum urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 87 publications
1
22
0
1
Order By: Relevance
“…Interviewer-administered semi-structured questionnaire (S1 File) will be used for data collection. The questionnaire will be developed from the review of related local literature, [12,24,26] and the oral examination will be based on the WHO Oral Health Surveys: Basic methods, 5 th Edition. [27].…”
Section: Baseline Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interviewer-administered semi-structured questionnaire (S1 File) will be used for data collection. The questionnaire will be developed from the review of related local literature, [12,24,26] and the oral examination will be based on the WHO Oral Health Surveys: Basic methods, 5 th Edition. [27].…”
Section: Baseline Data Collectionmentioning
confidence: 99%
“…[10][11][12] There is an unequal burden of oral diseases affecting those in the rural areas more than those in the urban communities, [13] and more among those living in slums than non-slum areas. [12] Most oral diseases like dental caries and periodontal problems are preventable. [9] Dental caries is one of the most common oral diseases that negatively impact the oral health-related quality of life of those affected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High incidence of plaque and calculus was also found among 66% of respondents in a survey done in Kwara State of Nigeria, with children aged 12 reporting higher incidence of plaque and gingivitis than the adult population while 13% incidence of dental caries was reported as the lowest oral condition in the state [7]. In a study done in Kano, a northern city in Nigeria, 49.8% of children and adults reported dental caries as the most common challenge [8], however, Osuh et al reported a higher prevalence of oral diseases among residents in slums compared with non-slum urban residents in Ibadan, a city in western Nigeria [9]. Oral health disease is on the increase in Nigeria and preventive strategy must be prepared after a comprehensive study on the spread of oral diseases is done.…”
Section: Introductionmentioning
confidence: 99%